Corporate Storytelling and Sustainability in Skincare Brand Websites: A Multimodal Discourse Analysis - Gisna Auliya; Sajidin; Lina Herlina (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
This study examines how corporate storytelling on skincare brand websites constructs sustainability and ethical values through multimodal discourse. Employing a qualitative descriptive approach, the research applies Multimodal Critical Discourse Analysis grounded in Kress and van Leeuwen’s visual grammar framework. The data comprise visual and verbal texts from the official websites of two skincare brands from different countries: From This Island (Indonesia) and Innisfree (South Korea). The analysis focuses on representational, interactive, and compositional meanings to uncover how brand values are ideologically framed and naturalized through multimodal resources. The findings indicate that both brands strategically mobilize visual grammar to legitimize sustainability and ethical claims, positioning them as integral to brand identity. The interplay between visual and verbal modes functions to enhance audience engagement and credibility while simultaneously commodifying ethical narratives. This study concludes that corporate storytelling on skincare websites operates as a strategic multimodal discourse that shapes consumer perception and reinforces corporate ideologies.